Environmental Justice Analysis: Theories, Methods, and Practice - Liu, Feng (CRC Press, 2009)
Is the environmental justice debate solely an economic issue? Is it a social issue as well as a moral, political, or science issue? In Environmental Justice Analysis: Theories, Methods, and Practice author Feng Liu suggests it is all of them. He presents a multi-perspective, multi-disciplinary, and inter-disciplinary approach to analyzing environmental justice issues.